Sliding mode speed control for DC drive systems - Guldemir, Hanifi (Association for Scientific Research, 2003)
In this study, the Sliding Mode Control theory of the Variable Structure System has been applied to the speed control of a dc motor. The dynamic performance of the sliding mode speed control system has been studied against system parameter variations and external load disturbance and the simulation results are given. The application of the sliding mode control theory to controller design for DC drive control system shows a robust system performance.
Keywords: DC motor; Sliding mode; Variable structure